2016
DOI: 10.1103/physrevb.93.035432
|View full text |Cite
|
Sign up to set email alerts
|

Doping-dependent intraband carrier dynamics in Landau-quantized graphene

Abstract: We investigate the intraband carrier dynamics in Landau-quantized graphene after an optical excitation with low-energetic terahertz pulses. Based on a microscopic theory, we calculate time-dependent differential transmission spectra reflecting the Landau-level dynamics. Our calculations reveal a strong dependence on the Fermi energy E F of the graphene sample as well as on the applied magnetic field B. We find that the pump pulse can lead to both absorption bleaching and absorption enhancement depending on B a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…While the carrier dynamics in graphene has been intensively investigated over the last years, there have been only a few studies on the dynamics in Landau‐quantized graphene . The first experiment was performed by Plochocka et al.…”
Section: Carrier Multiplicationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the carrier dynamics in graphene has been intensively investigated over the last years, there have been only a few studies on the dynamics in Landau‐quantized graphene . The first experiment was performed by Plochocka et al.…”
Section: Carrier Multiplicationmentioning
confidence: 99%
“…While the carrier dynamics in graphene has been intensively investigated over the last years, there have been only a few studies on the dynamics in Landau-quantized graphene [17,30,53,57,[59][60][61]. The first experiment was performed by Plochocka et al in 2009 [30], where rather high-energetic Landau levels (n ∼ 100) have been investigated.…”
Section: Carrier Multiplication In Landau-quantized Graphenementioning
confidence: 99%
“…In the past few years, much effort has been put towards studying carrier dynamics in Landau-quantized graphene under pulsed laser excitation 41 45 , The results showed that the Landau-level dynamics had a strong dependence on the Fermi energy and doping of the graphene sample, as well as the applied magnetic field. All these schemes are excited only by a pulsed laser without considering the continuous laser field.…”
Section: Introductionmentioning
confidence: 99%
“…The non-equidistant Landau level (LL) separation is an unique property of graphene when the perpendicular magnetic field is presented, which displays a number of interesting optical properties [1,2], such as the selection rule of the emission of polarized light [3], a giant Faraday rotation [4]and generation of entangled photon states [5]. In particular, the LL separation can be tuned from the infrared to terahertz regimes by manipulating the external magnetic field, which may be used as the infrared and terahertz sources for many electric devices [6][7][8][9][10][11]. Therefore, the studies of the non-radiative relaxation channels between LLs, competing with the optical transitions processes, are of crucial for the exploration of optical properties in the Landau-quantized graphene (LQG).…”
mentioning
confidence: 99%